Plasma-induced N doping and carbon vacancies in a self-supporting 3C-SiC photoanode for efficient photoelectrochemical water oxidation - Linyi Wu; Shuchang Guan; Binghua Zhou; Shien Guo; Jie Wang; Ling Wu; Gan Jet Hong Melvin; Josue Ortiz-Medina; Mingxi Wang; Hironori Ogata; Masaki Tanemura; Yoong Ahm Kim (The Royal Society of Chemistry, 2024)
Due to its suitable bandgap and excellent stability, 3C-SiC is being investigated as one of the promising candidates for photoelectrochemical (PEC) water oxidation. However, the limited surface activity and short carrier lifetime prevent 3C-SiC photoanodes from facilitating efficient PEC water splitting. To tackle these problems, this work proposes a plasma technique to control the crystal structure and optical characteristics of 3C-SiC. Nitrogen plasma induces carbon vacancies (Vc) and Si–N bonds, further leading to a narrower bandgap of 3C-SiC. The combination of Vc and N doping enhanced the light trapping capability of the electrode, thereby improving the efficiency of electron–hole pair separation and charge transfer, resulting in an accelerated water oxidation reaction, i.e., photocurrent density (2.50 mA cm−2 at 1.23 VRHE) increased by 7.6 times compared to that of pristine SiC. This work offers an effective strategy for regulating the electronic structure of SiC-based photoanodes by plasma treatment, which may be extended to other photoelectrodes for PEC application.